Strategi Mitigasi Risiko Usahatani Cabai Rawit: Sebuah Pendekatan Berlian Porter - Miswati Miswati; Dewi Kurniati; Josua Parulian Hutajulu (JSEP (Journal of Social and Agricultural Economics), 2023)
The productivity of cayenne pepper in Jawai District is lower than the productivity of cayenne pepper in South Jawai District, even though both have the same harvested land area. The low productivity of cayenne pepper in Jawai District is due to the high level of risk. This study aims to determine the level of production risk and income risk of cayenne pepper farming in Jawai District and to formulate alternative strategies to reduce farming risk levels. Analysis of the level of risk in agriculture using Coefficient of Variation (CV) analysis and formulation of alternative strategies using SWOT analysis with Porter's Diamond component indicators. The results showed that the risk level of production and income from cayenne pepper farming was 0.61 and 0.75, respectively, or more than 0.5, indicating a high level of risk. An alternative strategy that can be applied by farmers to reduce the level of risk is the WO (Weaknesses-Opportunities) strategy, which includes intensifying cayenne pepper farming, providing counseling to farmers regarding proper farming knowledge and management, conducting counseling related to knowledge of the use of agricultural technology, and extensification by expanding farming land cayenne pepper farming.